Domestic Violence and Education: Examining the Impact of Domestic Violence on Young Children, Children, and Young People and the Potential Role of Schools - Lloyd, Michele (Frontiers in Psychology, 2018)
This article examines how domestic violence impacts the lives and education of young children, children, and young people and how they can be supported within the education system. Schools are often the service in closest and longest contact with a child living with domestic violence; teachers can play a vital role in helping families access welfare services. In the wake of high profile cases of child abuse and neglect, concerns have been raised about the effectiveness of multi-agency responses to children living with abuse. In the UK, the case of four-year-old Daniel Pelka who died in 2012 following abuse and starvation by his mother, who experienced domestic violence, and her partner, led to a serious case review. It found recording systems in Daniel’s school were not used consistently, and details held by different agencies were not collated to enable the formation of a coherent assessment. The lack of integrated working cited in the report echoes findings from previous serious case reviews. A strong correlation exists between domestic abuse and child abuse, with approximately half of all domestic violence situations involving direct child abuse. Children can also be affected indirectly by violence occurring in their home by seeing or hearing it taking place. This article examines the impact of domestic violence on the mental health of children, and the impact on their education. Violence in children’s lives often causes disruption to their schooling and harms the quality of their educational experiences and outcomes. The abuse children experience can result in emotional trauma, physical and psychological barriers to learning, and disruptive behavior in school, while the underlying causes of these problems remain hidden. Knowing when and how to seek advice from multi-agency professionals is an essential part of effective practice among school staff. Despite their vital role in identifying signs of abuse and signposting referral pathways, research indicates teachers often lack confidence and knowledge for such work. The article examines how the professional learning and professional confidence of teachers can be developed, and how recent policy and practice developments in the UK have the potential to influence work in this area.